To make the expression (-5+ ? )+ (8 * 1/8) + c equivalent to c, we need to find the number that, when added to -5 and multiplied by 1/8, equals zero.
Let's solve for the missing number:
(-5 + ?) + (8 * 1/8) + c = c
The term (8 * 1/8) simplifies to 1:
(-5 + ?) + 1 + c = c
Combine like terms:
-5 + ? + 1 + c = c
-4 + ? + c = c
Isolate the missing number:
? = c - c + 4
? = 4
Therefore, the missing number that makes the expression equivalent to c is 4.
Enter the number that makes the expression below equivalent to c
(-5+ ? )+ (8 * 1/8) + c
1 answer